Light microscopic histology of supraspinatus tendon ruptures - Longo, Umile Giuseppe; Franceschi, Francesco; Ruzzini, Laura; Rabitti, Carla; Morini, Sergio; Maffulli, Nicola; Forriol, Francisco; Denaro, Vincenzo (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2007)
We analysed the morphological features of the human surgical specimens of supraspinatus tendon from patients with rotator cuff tears. Tendon samples were harvested from 31 subjects (21 men and 10 women; mean age 51 years, range 38–64) who underwent arthroscopic repair of a rotator cuff tear, and from five male patients who died of cardiovascular events (mean age, 69.6 years). Histological examination was performed using Haematoxylin and Eosin, Masson's Trichrome and Van Gieson's connective tissue stain. The specimens were examined twice by the same examiner under white light and polarized light microscopy. Particular effort was made to assess any evidence of the changes associated with tendinopathy. Within each specific category of tendon abnormalities, the chi‐square test showed significant differences between the control and ruptured tendons ( P < 0.05). Using the kappa statistics, the agreement between the two readings ranged from 0.57 to 0.84. We found thinning and disorientation of collagen fibres and chondroid metaplasia to be more pronounced on the articular side of the specimens from patients with rotator cuff tear ( P < 0.05). The present study provides a description of the histological architecture of human surgical specimens of normal supraspinatus tendon from patients with rotator cuff tears and demonstrates more frequent tendon changes on the articular side of the rotator cuff.